Surfactant-based prophylaxis and therapy against COVID-19: A possibility. (October 2020) - Pramod, K.; Kotta, Sabna; Jijith, U.S.; Aravind, A.; Abu Tahir, M.; Manju, C.S.; Gangadharappa, H.V.
Abstract: Hand hygiene by washing with soap and water is recommended for the prevention of COVID-19 spread. Soaps and detergents are explained to act by damaging viral spike glycoproteins (peplomers) or by washing out the virus through entrapment in the micelles. Technically, soaps come under a functional category of molecules known as surfactants. Surfactants are widely used in pharmaceutical formulations as excipients. We wonder why surfactants are still not tried for prophylaxis or therapy against COVID-19? That too when many of them have proven antiviral properties. Moreover, lung surfactants have already shown benefits in respiratory viral infections. Therefore, we postulate that surfactant-based prophylaxis and therapy would be promising. We believe that our hypothesis would stimulate debate or new research exploring the possibility of surfactant-based prophylaxis and therapy against COVID-19. The success of a surfactant-based technique would save the world from any such pandemic in the future too.